The securitized workplace: document protection, insider threats and emerging ethnographic barriers in a South Korean organization. Issue 3 (21st May 2021) - Prentice, Michael M.
Abstract : Purpose: The purpose of this paper is to demonstrate how document protection has become a key object of concern for organizations, how the threat of leaks has led to an increase in security technologies and policies and how these developments present new and emergent ethnographic challenges for researchers. Through a study of a South Korean organization, the paper aims to demonstrate the ways workplace documents are figured into wider legal, regulatory and cyber security concerns. Design/methodology/approach: The research is based on 12 months of intensive embedded fieldwork in a South Korean firm from 2014 to 2015 and follow-up interviews in 2018. The author followed an immersive and inductive approach to collecting ethnographic data in situ . The author was hired as an intern in a Korean conglomerate known as the Sangdo Group where he worked alongside Human Resources managers to understand their work practices. The present article reflects difficulties in his original research design and an attempt to analyze the barriers themselves. His analysis combines ideas from theories of securitization and document studies to understand how the idea of protection is reshaping workplaces in South Korea and elsewhere. Findings: The paper highlights three findings first that South Korean workplaces have robust socio-material infrastructures around document protection and security, reflecting that security around document leaks is becoming integrated into normal organizational life. Second, the securitization of document leaks is shifting from treating document leaks as a threat to organizational existence, to a crime by individual actors that organizations track. Third, that even potential document leaks can have transitive effects on teams and managers. Originality/value: Organizational security practices and their integration into workplace life have rarely been examined together. This paper connects Weber's insights on bureaucratization with the concept of securitization to examine the rise of document security practices and policies in a South Korean organization. The evidence from South Korea is valuable because technological developments around security coupled with organizational complexities portend issues for other organizational environments around the world.